(untitled) (American Journal of Smart Technology and Solutions, 2024)
In the dynamic landscape of Afghanistan’s education, this study explores into the transformative integration of the Internet of Things (IoT). With the purpose of scrutinizing perceptions, challenges, and preparedness, a meticulous mixed-methods approach was employed, collecting data from 120 participants across diverse educational backgrounds. The deliberate inclusion of participants from Computer Science, Agriculture, Education, and Economics faculties, representing institutions such as Kabul, Karwan, Badakhshan, Samangan, and Faryab University, ensured a comprehensive exploration. Through structured questionnaires utilizing Likert-scale items, the methodology sought to gauge participants’ perceptions of technological infrastructure, institutional support, and challenges linked to IoT integration. Notably, ANOVA and regression analyses were applied to discern influential factors shaping participants’ views. The study’s novelty lies in its meticulous uncovering of nuanced perceptions, specifically emphasizing the pivotal role of technical expertise perception in the readiness for IoT integration within educational faculties. The consensus on IoT’s potential to reshape teacher-student interactions and elevate academic outcomes is a novel contribution, highlighting the transformative impact on pedagogical practices. Additionally, the research anticipates and scrutinizes technological and infrastructural challenges, identifying resource constraints, and proposing targeted strategies for efficacious IoT implementation. In conclusion, this research enriches the discourse on IoT in education by accentuating the significance of institutional support, addressing challenges, and proposing practical guidelines. It not only contributes actionable insights for Afghanistan policymakers and educators but also lays a foundation for future research to optimize strategies in specific challenges, ultimately fostering successful IoT integration in Afghanistan’s educational landscape.